A Hybrid FETD-FDTD Method with Nonconforming Meshes (Communications in Computational Physics, 2011)
A quasi non-overlapping hybrid scheme that combines the finite-differencetime-domain (FDTD) method and the finite-element time-domain (FETD) method withnonconforming meshes is developed for time-domain solutions of Maxwell's equations.The FETD method uses mixed-order basis functions for electric and magneticfields, while the FDTD method uses the traditional Yee's grid; the two methods arejoined by a buffer zone with the FETD method and the discontinuous Galerkin methodis used for the domain decomposition in the FETD subdomains. The main features ofthis technique is that it allows non-conforming meshes and an arbitrary numbers ofFETD and FDTD subdomains. The hybrid method is completely stable for the timesteps up to the stability limit for the FDTD method and FETD method. Numericalresults demonstrate the validity of this technique.